2020
DOI: 10.3390/vetsci7010016
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Embryo Recovery in Holstein Cows Treated by Intra-Ovarian Platelet Rich Plasma before Superovulation

Abstract: The current research was designed to evaluate if intra-ovarian administration of autologous platelet rich plasma (PRP) before superovulation could increase the number of follicles responsive to gonadotropin treatment in order to improve embryo recovery in donor cows. Eight Holstein-Friesian cows of proven fertility were employed. After estrous synchronization, at the 18th day of diestrous, the right ovary of each cow was left untreated and served as control while the left ovary was inoculated with 5 mL of PRP.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 25 publications
0
21
1
1
Order By: Relevance
“…The results of our study are in accordance with what has been previously reported by Sills et al [ 34 ] in humans. Furthermore, intraovarian injection of autologous PRP before superovulation resulted in higher follicular growth and blastocyst development in vivo in Holstein cows [ 14 ]. The mechanism by which L-GF equina could stimulate follicular growth and blastocyst development is not entirely clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of our study are in accordance with what has been previously reported by Sills et al [ 34 ] in humans. Furthermore, intraovarian injection of autologous PRP before superovulation resulted in higher follicular growth and blastocyst development in vivo in Holstein cows [ 14 ]. The mechanism by which L-GF equina could stimulate follicular growth and blastocyst development is not entirely clear.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, PRP contains cytokines such as platelet factor 4 (PF4) and CD40 ligand (CD40L) [ 13 ]. Treatment with PRP is a valuable therapy for improving the embryo recovery in superovulating cows [ 14 ]. Furthermore, it has been used to increase fertility in cows with ovarian hypofunction [ 15 ] and to increase the pregnancy rate in repeat breeding of pure Arabian mares [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the treated group animal, the intraovarian PRP injection was performed under ultrasound guidance using a Madison SA 600v instrument equipped with an ovum pick up probe (PB-06VE65/20BD) as described by Cremonesi et al ( 20 ). Each animal was restrained in a cattle cage and clipped over the S5-C1 vertebrae (5 × 5 cm).…”
Section: Methodsmentioning
confidence: 99%
“…Research from Milan [20] described bovine response to administration of autologous intraovarian PRP before programmed superovulation. A significant improvement was noted in mean follicle number between control vs. PRP injected ovaries, and significantly more high-grade blastocysts were generated following PRP use [20].…”
Section: Ovarian Prp: Veterinary and Human Researchmentioning
confidence: 99%
“…Research from Milan [20] described bovine response to administration of autologous intraovarian PRP before programmed superovulation. A significant improvement was noted in mean follicle number between control vs. PRP injected ovaries, and significantly more high-grade blastocysts were generated following PRP use [20]. Additional animal experiments have found a beneficial (rescue) effect of PRP on ovarian function in female rats with ovarian damage induced by cyclophosphamide, concluding this approach could lead to improved primordial, primary, secondary, and antral follicle counts [21].…”
Section: Ovarian Prp: Veterinary and Human Researchmentioning
confidence: 99%